Neonatal mortality and associated factors in the specialized neonatal care unit Asmara, Eritrea - Andegiorgish, Amanuel Kidane (BMC Public Health, 2020)
BACKGROUND: Limited knowledge on the magnitude of neonatal mortality and associated factors is hampering early intervention in African countries. Objective: To determine neonatal mortality and associated factors in the Specialized Neonatal Care Unit Asmara, Eritrea. METHODS: Medical records of all neonates admitted to the Specialized Neonatal Care Unit in 2016 were reviewed using a cross-sectional study. The most important causes of admission and mortality were analyzed. Univariate and multivariate logistic regression analysis was used to evaluate the strength of risk factors associated with neonatal mortality. Variables significant at P < 0.20 level in the univariate analysis were retained in the multivariate model. Model fit was evaluated using Hosmer and Lemeshow test (Chi-square = 12.89, df = 8; P = 0.116), implies the model’s estimates fit the data at an acceptable level. Collinearity was assessed using variance inflation factor (VIF) < 4. P-value < 0.05 was considered statistically significant. RESULTS: Of the 1204 (59.9% boys and 40.1% girls) neonates admitted in 2016, 79 (65.6/1000 live births) died. The major causes of admission were sepsis (35.5%), respiratory distress syndrome (15.4%) and perinatal asphyxia (10%). Major causes of death were respiratory distress syndrome (48.1%); extremely low birth weight (40.9%) and very low birth weight (30.5%). After adjustment, low birth weight (Adjusted odds ratio (AOR) = 4.55, 95% CI,1.97–10.50), very low birth weight (AOR = 19.24, 95% CI, 5.80–63.78), late admission (24 h after diagnosis) (AOR = 2.96, 95% CI, 1.34–6.52), apgar score (in 1 min AOR = 2.28, 95% CI, 1.09–4.76, in 5 min AOR = 2.07, 95% CI, 1.02–4.22), and congenital abnormalities (AOR = 3.95, 95% CI, 1.59–9.85) were significantly associated with neonatal mortality. Neonates that stayed > 24 h in the Specialized Neonatal Care Unit (AOR = 0.23, 95% CI, 0.11–0.46) had a lower likelihood of death. Overall 95.8% of mothers of neonates attended antenatal care and 96.6% were facility delivered. None of the maternal conditions were associated with neonatal mortality in this study. CONCLUSIONS: Low birth weight, late admission, low apgar scores and congenital abnormalities were significantly associated with neonatal mortality in the Specialized Neonatal Care Unit. Early management of low birth weight, preterm births, and neonatal complications should be the priority issues for controlling local neonatal deaths.